Obtaining of fermented drinks from hawthorn fruits - Kosogolova, L.O.; Kuznietsova, O.O.; Turbovska, S.V. (Problems of Environmental Biotechnology, 2021)
The parameters of extraction of extractives from hawthorn fruits are investigated in the article. The optimal ratio of the components of the fermented drink, namely, ratio as 60 to 40 of aqueous extract of hawthorn fruit and barley-malt extract was selected. The optimal parameters of wort fermentation with hawthorn fruit extract were determined. The fermentation duration is 5 days. The rational ratio of the components of the fermented drink using hawthorn extract has been established. Physico-chemical and organoleptic parameters of the finished fermented drink are determined.